(untitled) (REVISTA DIREITOS, TRABALHO E POLÍTICA SOCIAL, 2023)
This article aims to map and analyze the cases of violence against sexual and gender diversity registered, through Police Reports, in Police Stations of the Secretariat of Public Security of the State of Sergipe (SSP/SE) in Brazil, between 2015 and 2018, verifying how the phenomena of underreporting, revictimization and intersectionality are present in these complaints. The mapping was carried out in the intranet system of the Secretariat of Public Security of the State of Sergipe – Brazil (SSP/SE). Using 32 (thirty-two) keywords, 5.100 (five thousand and one hundred) complaints were found in 71 (seventy-one) Police Stations, in which 305 (three hundred and five) Police Reports were selected. The methodology was based on a qualitative-quantitative, descriptive, and documentary analysis. Most of the complaints analyzed present the phenomena of underreporting, revictimization and intersectionality of oppression, which require joint and transversal responses.